The Role of Exosomes in Pancreatic Cancer From Bench to Clinical Application: An Updated Review - Chen, Kai; Wang, Qi; Kornmann, Marko; Tian, Xiaodong; Yang, Yinmo (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the most dismal gastrointestinal malignancies with an overall 5-year survival rate of 8%-9%. The intra-tumor heterogeneity and special tumor microenvironment in PDAC make it challenging to develop effective treatment strategies. Exosomes are extracellular vesicles that originate from the endosomes and have a diameter of 40-160 nm. A growing body of evidence has shown that exosomes play vital roles in tumor initiation and development. Recently, extensive application of exosomes as biomarkers and drug carriers has rendered them attractive in the field of PDAC. This review summarizes the latest progress in the methodologies for isolation, modification, and tracking of exosomes, exosome-mediated cell-to-cell communication, clinical applications of exosome as minimally invasive liquid biopsy and drugs carriers, as well as their involvement in the angiogenic regulation in PDAC. In spite of these advancements, some obstacles are still required to be overcome to use the exosome-based technologies for early diagnosis or improvement of prognosis of patients with PDAC.